Knowledge Management as a Catalyst for Institutional Performance (Empirical Study at Private Universities in the Pantura Region of West Java) - Rita Sri Silvia Pamuji; Hilmiana Hilmiana (Dinasti Publisher, 2025)
When it comes to enhancing the efficiency of educational institutions, knowledge management plays a crucial role. This study aims to analyse the role of knowledge management in improving the performance of Private Universities in the Pantura region of West Java. As a first step in the research process and creating a research model, this study employs a quantitative descriptive approach to describe the actual conditions using data gathered from questionnaires based on first-hand observation of research objects and interviews. During this phase, researchers gather information and preliminary data through observations. Subsequent study systematically defines the features or functions of a phenomenon within a certain population, emphasising what happens and how it can happen. In this method, 315 faculty members with at least two years of experience as permanent lecturers at private university foundations fill out a questionnaire based on the knowledge management model and higher education performance indicators. The purpose of this survey is to examine potential relationships between the variables. The direct influence of knowledge management on university performance was tested through data analysis utilising the Structural Equation Modelling (SEM) approach. According to the study's conclusions, university performance is positively affected by knowledge management. This conclusion reinforces the significance of enhancing knowledge management to boost university competitiveness. In order to create policies for the long-term development of knowledge management, university administrators might look to the research's practical consequences.